2019
DOI: 10.1186/s13287-019-1278-x
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-specific exosomes promote the odontogenic differentiation of human dental pulp stem cells (DPSCs) through TGFβ1/smads signaling pathway via transfer of microRNAs

Abstract: Background Exosomes derived from dental pulp stem cells (DPSCs) can be used as biomimetic tools to induce odontogenic differentiation of stem cells, but the regulatory mechanisms and functions of exosome-encapsulated microRNAs are still unknown. The present study aimed to clarify the role of microRNAs contained in the exosomes derived from human DPSCs and their potential signaling cascade in odontogenic differentiation. Methods Exosomes were isolated from human DPSCs cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(117 citation statements)
references
References 39 publications
3
110
0
Order By: Relevance
“…By analysis of the effects of MSC-exomiRNAs, some targeted genes were identified which contribute to specific pathways related to cell death and cell growth, and pathways related to fibrosis such as Wnt signaling, PDGF, and TGF-β [ 63 ]. In another study it was found that lineage-specific exosomes could promote the odontogenic differentiation of human dental pulp stem cells (DPSCs) through the TGFβ1/Smad signaling pathway via transfer of miRNAs such as miR-27a-5p [ 64 ].…”
Section: Mesenchymal Stem Cells As Therapeutic Toolsmentioning
confidence: 99%
“…By analysis of the effects of MSC-exomiRNAs, some targeted genes were identified which contribute to specific pathways related to cell death and cell growth, and pathways related to fibrosis such as Wnt signaling, PDGF, and TGF-β [ 63 ]. In another study it was found that lineage-specific exosomes could promote the odontogenic differentiation of human dental pulp stem cells (DPSCs) through the TGFβ1/Smad signaling pathway via transfer of miRNAs such as miR-27a-5p [ 64 ].…”
Section: Mesenchymal Stem Cells As Therapeutic Toolsmentioning
confidence: 99%
“…Although the main substance contained in conditioned medium and exerting therapeutic effects has not been clarified, exosomes might play an important role in regenerative processes. Exosomes derived from DPSCs increased the odontogenic differentiation of DPSCs [ 146 ] and promoted the regeneration of dental pulp-like tissue [ 147 ]. In addition, Li et al demonstrated that exosomes derived from SHEDs suppressed neuroinflammation when they were transplanted into a rat brain injury model [ 148 ].…”
Section: Regenerative Capacity Of Dpscs and Shedsmentioning
confidence: 99%
“…The cell signaling pathways by which hDPSC-EXOs regulate angiogenesis in an in ammatory environment remain unclear. Exosomal microRNAs negatively regulate the expression of their target genes by binding to the 3'UTRs of the target genes, causing translational repression [29,30]. By conducting microRNA sequencing, we found that the expression of certain microRNAs was downregulated/upregulated in the LPS-hDPSC-EXOs.…”
Section: Discussionmentioning
confidence: 92%